2018
DOI: 10.1039/c8gc00348c
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed efficient reduction of ketones in water with formic acid as a hydride donor at low catalyst loading

Abstract: Simple and functionalized ketones are readily reduced in water with very low catalyst loading using formic acid as a hydride donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 56 publications
5
36
1
Order By: Relevance
“…A reaction mechanism for the reduction of aldehydes in the presence of INP-TPA-POP was proposed according to the literature as shown in Scheme 5. [35][36][37][38] Accordingly, the formate anion can coordinate with catalyst metal center (II) to form iridium hydride (III) by evaluation of carbon dioxide. [39] In this situation, the formed Ir-hydride centers can trap aldehyde to transfer the hydride to the carbon of carbonyl group probably via a four-member ring transition state.…”
Section: The Catalytic Application Of Immobilized Iridium Nanopartimentioning
confidence: 99%
“…A reaction mechanism for the reduction of aldehydes in the presence of INP-TPA-POP was proposed according to the literature as shown in Scheme 5. [35][36][37][38] Accordingly, the formate anion can coordinate with catalyst metal center (II) to form iridium hydride (III) by evaluation of carbon dioxide. [39] In this situation, the formed Ir-hydride centers can trap aldehyde to transfer the hydride to the carbon of carbonyl group probably via a four-member ring transition state.…”
Section: The Catalytic Application Of Immobilized Iridium Nanopartimentioning
confidence: 99%
“…[4][5][6][7][8] However, due to environmental and ecological advantages and reaction-specic pH selectivity, using water as the solvent for the TH of ketones is very convenient and attractive compared to traditional organic solvents. [9][10][11][12] Two hydrogen sources have primarily been used in TM-catalyzed TH, namely isopropanol and formic acid. The conception of metalligand bifunctional cooperation is oen used to explain the reaction mechanism of TH and the HH of polar double bonds catalyzed by TM complexes with different ligand environments such as diphosphine-diamine ruthenium catalyst A (see Scheme 1) [13][14][15][16][17][18][19] as well as those of TH using formic acid hydrogen sources.…”
Section: Introductionmentioning
confidence: 99%
“…A number of TH reactions of polar double bonds catalyzed by cyclometallated TM complexes have been developed in the past decades. 11,[24][25][26][27] Most of the TM catalysts for ketone/imine hydrogenation have a Lewis acidic site in the TM center and a Lewis basic site in the ligand moiety of the structure (TM-LB catalyst) or a Lewis basic site in the TM center and a Lewis acidic site in the ligand moiety (TM-LA catalyst). 2,28 In 1986, Shvo et al reported a useful TH catalyst (B in Scheme 2) for ketones, which is an example of a ligand-metal bifunctional catalyst wherein the redox activity is distributed between the metal center and a cyclopentadienone ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have achieved reduction of some ketones in water with formic acid. In their study, they have demonstrated that TH reduction rates of some ketones are dependent on the pH values and catalyst TC‐7 (Iridium catalyst) have behaved best at pH=1.5, resulting in an 88% conversion . Yang et al.…”
Section: Introductionmentioning
confidence: 99%